Dampak dan Konsekuensi Pernikahan Sesama Marga dalam Komunitas Karo Pada Masyarakat Karo di Berastagi - Gita, Endah Rananda; Sakinah, Nurul; Sazali, Hasan; Dalimunthe, Maulana Andinata (Journalism, Public Relation and Media Communication Studies Journal (JPRMEDCOM), 2023)
The Karo people are one of the ethnic groups in Indonesia, especially in the North Sumatra region. The Karo community has strong traditions when it comes to family ties and marriage. However, in some cases, inter-clan marriages within Karo society have caused strong reactions, leading to the displacement of affected families. This research was conducted to help the younger generation better understand the impact of inter-clan marriages in Karo society. It helps us to understand the internal and external conflicts that occur and their impact on family relationships, social interactions, community and youth support. In addition, this research also aims to identify solution approaches that young people can apply in their lives. Quantitative research methods were used in this study. Qualitative methods, i.e. Collecting and reviewing the quality and accuracy of field survey data and answering questions related to the theory of literature study on the issue. This research concludes that marriage between clans (Turang) is considered a violation of customs and the perpetrator is punished according to the customs of the community and tribe. When an inter-tribal marriage occurs, the children have the same clan and surname and are not automatically accepted by the Karo tribe.